FISHING CAMP DALAM RUANG MELENGKAPI SEA WORLD DENGAN KONSEP SUASANA DI BAWAH LAUT - I Wayan Raditya Sai Pratama; Ngurah Gde Dwi Mahadipta; A.A Gde Tugus Hadi Iswara (Jurnal PATRA, 2019)
Indonesia is the largest archipelagic country in the world with diverse marine biota. However, there are still many people who do not know that this is the education needed and become one of the tourist destinations. Therefore Sea World was created to educate the public about marine air and fresh air with additional fishing camp facilities that can be a means of entertainment for people who have a hobby of shopping and provide a refreshing means of daily activities. The method used in data collection is a method of collecting data based on sources, namely primary data and secondary data as well as sources of physical and non-physical data forms. From the data collection method obtained data collected design Sea World and Fishing Camp in Denpasar City, then carried out analysis with qualitative and quantitative methods. In interior design using utopia methods with beautiful underwater interiors. It is expected that the design of Sea World and Fishing Camp can provide entertainment and education facilities that have facilities under the sea.